Algiers [videorecording (DVD)] - Cromwell, John, 1886-1979; Boyer, Charles, 1899-1978; Lamarr, Hedy, 1913-2000; Gurie, Sigrid, 1911-1969; Ashelbe (Front Row Entertainment, 2001)
Charles Boyer plays Pepe le Moko, a notorious thief hiding out in the Casbah, who falls in love with a wealthy tourist, played by Heddy Lamarr.